Strategi Karyawan Dalam Meningkatkan Minat Anggota Menabung Dibmt Maslahah Cabang Gondangwetan Pasuruan - Mita Amelia Pratiwi; Saiful Bakhri; Ilham Wahyudi (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2024)
Baitul Maal wa Tamwil (BMT) Maslahah Gondang Wetan Pasuruan Branch is a financial institution that implements a system based on Islamic sharia. In our business activities, we apply the principle of profit sharing (nisbah) and not the principle of profit sharing (riba) to guarantee halal income. The goal of every company is to create satisfied customers. Satisfying and retaining customers requires the right service strategy. The aim is to provide customer service and satisfaction so that customers can find out the reasons why customers are interested in saving, namely the quality of service and the public's reaction to customer satisfaction at BMT Maslaha, Gondang Wetang Branch, Pasuruan Branch. I am positive about the presence of BMT Maslaha Gondan Wetang Branch Pasuruan Branch because the service provided by officers at BMT Maslaha Gondan Wetang Branch Pasuruan Branch is very good. This public recognition is mainly due to the performance of the employees of BMT Maslaha, Gondan Wetang Branch and Pasuruan Branch, all of whom are Islamic boarding school graduates and have positive attitudes among their 4,444 active members. Apart from that, BMT Maslaha, Gondangwetang and Pasuruan savings products are always available for urgent needs and profit sharing is carried out every month. The relatively easy process is also the reason members choose to save at the BMT Maslaha Gondang Wetang Branch, Pasuruan Branch. In this case the researcher uses case study research by directly investigating the research topic. Employees of the Pasuruan branch of BMT Maslaha Gondan Wetang are being tested here. The aim of this research approach is to identify employee strategies in increasing customers' interest in saving at the Pasuruan branch of BMT Maslaha Gondang Wetang.The researcher's data source is an important factor to consider when deciding on data collection methods. The data sources used in this research are primary data and secondary data